Physical, Chemical, and Biological Parameters of Water in Semi-intensive Vannamei Shrimp (Litopenaeus vannamei) Pond - Putra, Angga Syah; Febri, Suri Purnama; AS, Agus Putra; Azmi, Fauziah (Jurnal Ilmiah Samudra Akuatika, 2024)
This research aims to analyze and determine the physical, chemical and biological parameters of water in the best semi-intensive ponds for cultivating vannamei shrimp. The method used is a descriptive survey, namely sampling is carried out directly in the field. Based on the research results, the physical parameters obtained ranged from 26.33 – 26.67 ppt, temperature 30.43-30.86 oC, depth 113.33 – 120 cm, brightness 39.50 – 46.66, TDS 582.83 – 587.17 ppm, TSS 22.40 – 24.83 ppm. The chemical parameters obtained range from DO 5.56 – 6.76 mg/L, pH 7.71 – 7.89, alkalinity 162.37 – 184.94 mg/l, nitrate 3.72 – 4.22 mg/l, TAN 0.043 – 0.061 mg/l, phosphate 0.019 – 0.062 mg/l while the parameters that are not optimal are nitrite 1.39 – 1.52 mg/l. The biological parameters obtained by phytoplankton in ponds A, B and C were Chatoceros, Dinobryon, Lingulodinium, Nodularia, Oscillatoria, Planktothrix, Proboscia and cochlodinium species. Meanwhile, the zooplankton found in ponds A, B, C are Acartia, Nematodes and Nitocras pinipes.